El Estado es el Otro: la atención de la violencia contra las mujeres en las zonas rurales del Perú - Crisóstomo Meza, Mercedes (2021)
“The state does not know the situation and needs of the people” is a prevalent notion in women who suffer violence and turn to the state searching justice and officials who work in the institution responsible for preventing, punishing, and responding to such violence. This article answers: what are the facts that lead to creating this notion about the state as “other” in women victims of violence and in officials who work in the state? Using the ethnographic methodology and concepts about violence against women, formation of the state and political neo-institutionalism, I analyse the functioning of the state in dealing with violence against women who live in the rural areas of Ayacucho and Huancavelica. This article concludes that the state policies to address violence against women have been designed based on urban population but above all with monolithic, homogeneous, and centralist visions of the state and the population. The analysed cases show that these features consolidate a vision of the state as “other”, distant, arbitrary, and distant, thus, undermining the legitimacy of the state itself.